2018
DOI: 10.1186/s12864-018-4954-9
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA-seq analysis of single porcine blastocysts revealed that maternal estradiol-17beta exposure does not affect miRNA isoform (isomiR) expression

Abstract: BackgroundThe expression of microRNAs (miRNAs) is essential for the proper development of the mammalian embryo. A maternal exposure to endocrine disrupting chemicals during preimplantation bears the potential for transgenerational inheritance of disease through the epigenetic perturbation of the developing embryo. A comprehensive assembly of embryo-specific miRNAs and respective isoforms (isomiR) is lacking to date. We aimed at revealing the sex-specific miRNA expression profile of single porcine blastocysts d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 80 publications
2
14
0
Order By: Relevance
“…Several studies have also used Y chromosome-linked genes to determine the sex of pigs at early development stages [13,18,19], however, all of them have applied DNA-based approaches. The Y chromosome harbors genes that are essential for testis development and function, such as the master gene for testis determination (SRY), which is expressed during a critical period of embryonic development, and other genes that are important for spermatogenic function, as the ZFY, EIF1AY and KDM5D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also used Y chromosome-linked genes to determine the sex of pigs at early development stages [13,18,19], however, all of them have applied DNA-based approaches. The Y chromosome harbors genes that are essential for testis development and function, such as the master gene for testis determination (SRY), which is expressed during a critical period of embryonic development, and other genes that are important for spermatogenic function, as the ZFY, EIF1AY and KDM5D.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated how to identify the conceptuses sex at early stages of development using molecular techniques, as PCR (polymerase chain reaction) from Y chromosome-linked genes [13,[18][19][20]. The PCR provides sensitive, precise, rapid, and reliable results [20].…”
Section: Introductionmentioning
confidence: 99%
“…1 EVs-extracellular vesicles; 2 ULFs-uterine luminal flushings; 3 CM-conditioned media Intriguingly, porcine endometria [23] as well as blastocysts [38] are abundant not only in canonical miRNAs but also isomiRs-widely reported variants of miRNAs-which have been proven to work cooperatively [43]. Many miRNAs can be co-expressed with their isomiRs and/or other members of the family (e.g., 23a/b, 148a/b in the porcine endometrium), resulting in wider or stronger biological effects.…”
Section: Mirnas At the Embryo-maternal Interfacementioning
confidence: 99%
“…A previous study has shown that highly expressed miRNAs may play vital roles in the regulation of embryo implantation [30]. The expression of top 20 most highly expressed known miRNAs in ULF exosomes was compared with that in endometrium [31] and embryo [29] collected on D10. Among these miRNAs, ssc-miR-21-5p was the most abundant in all libraries.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the expression of miRNAs in porcine ULF exosomes is related to that of miRNAs in endometrium and embryos during peri-implantation period, the expression of top 20 highly expressed known miRNAs in ULF exosomes was compared with that in embryos and endometrium at D10 [29]. The results indicated that most of these miRNAs were expressed in both the embryo and endometrium (Additional file 6: Table S5).…”
Section: Functional Analysis Of Target Genes Of Highly Expressed Knowmentioning
confidence: 99%